Erosion of EUROFER steel by mass-selected deuterium ion bombardment. (August 2018) - Sugiyama, K.; Balden, M.; Elgeti, S.; Höschen, T.; Oberkofler, M.; Roth, J.; Jacob, W.
Highlights: EUROFER has been eroded by deuterium ions to fluences of several 10 24  atoms/m 2 . Resulting sputter yields deviate considerably from SDTrimSP simulations. Tungsten surface enrichment is observed e.g. in Rutherford backscattering. Resulting surface morphologies have strong grain dependencies. Morphology evolution is a key parameter affecting the sputter yield. Abstract: The erosion behaviour of EUROFER steel due to mono-energetic deuterium (D) ion bombardment in the energy range of 100–1000 eV/D was investigated. At low fluences, the sputtering yield is comparable to that of pure iron (Fe). It then decreases with increasing fluence and tends toward a steady state at larger fluences. The largest experimentally investigated fluences are of the order of several 10 24 D/m 2 . The yield reduction is more pronounced for lower D impinging energies. A simple model is presented within which the evolution of the yield can be described by an exponential decay, using empirical values for the fitting parameters. In this model, the yield reduction is caused by preferential sputtering of Fe and the consequent development of a tungsten- (W-) enriched surface layer. SDTrimSP simulations also confirm the appearance of a W-enriched surface layer. However, the experimentally observed fluence dependence of the sputtering yield could not satisfactorily be reproduced in these simulations. The resulting enrichment layer thicknesses below 1 Å stretch the physics model implemented in SDTrimSP beyond its validity range. Experimentally, surface enrichment of W was qualitatively confirmed in Rutherford backscattering and sputter X-ray photoelectron spectroscopy measurements. However, the measured depth profiles are very likely influenced by the observed surface roughening caused by the D irradiation. Electron microscopy revealed the inhomogeneous W distribution on the un-irradiated sample as well as a grain-dependence of erosion and grain-dependent topography development. The inclusion of surface topography in the description of the erosion could be the key to improve the agreement between model predictions and the experiment.